Helicobacter pylori-Mediated Oxidative Stress and Gastric Diseases: A Review - Han, Lu; Shu, Xu; Wang, Jian (Frontiers in Microbiology, 2022)
Gastric cancer is considered to be a type of gastrointestinal tumor and is mostly accompanied by Helicobacter pylori (HP) infection at the early stage. Hence the long-term colonization of the gastric mucosa by HP as a causative factor for gastrointestinal diseases cannot be ignored. The virulence factors secreted by the bacterium activate the signaling pathway of oxidative stress and mediate chronic inflammatory response in the host cells. The virulence factors also thwart the antibacterial effect of neutrophils. Subsequently, DNA methylation is induced, which causes continuous cell proliferation and evolution toward low-grade-differentiated gastric cells. This process provides the pathological basis for the occurrence of progressive gastric cancer. Therefore, this review aims to summarize the oxidative stress response triggered by HP in the gastric mucosa and the subsequent signaling pathways. The findings are expected to help in the formulation of new targeted drugs for preventing the occurrence of early gastric cancer and its progression to middle and advanced cancer.